From Time to Time: A Constructivist Approach to Sociality in Learning - Mancini, Francesco; Glusac, Tanja (2018, Editorial Universitat Politècnica de València, 2018)
Under the current financial pressures, tertiary education increasingly looks towards the corporate sector to import its model of management and efficiency. While benefits of this model can be seen in practice, in regard to staff and facilities management and financial viability, its impact on teaching and learning is causing a disruption to the very core of tertiary education, eroding sociality in learning and opportunities for sharing knowledge and values. Capacity to work in teams and ability to critically solve problems by collaborating and sharing insights and information are skills students are expected to gain during their studies. The development of these skills to their fullest using Design Thinking approach, however, is currently not widely supported, albeit desirable, in the present education context which is addressing the efficiency of time management by reducing contact time, increasing student/staff ratio and shifting towards integrated and mass education modes of delivery. While this paper is not disputing the existing model, it responds to its current challenges proposing a stronger integration of different factors contributing to learning. The aim is to present a collaborative working model as a way of bridging ‘the missing link between theoretical findings [on holistic and interdisciplinary learning] and demands by pedagogy science’. Such a model is envisioned to encourage sociality in learning and strategize space/time/experience management, ultimately enhancing knowledge and value sharing. Keywords: Design Thinking; Constructivism; Experiential Learning; Sociality; Studio Culture.